Um novo paradigma na Doutrina Social da Igreja - Andrade, Paulo Fernando Carneiro de (Revista eclesiástica brasileira, 2019)
The Social Teaching of the Church constitutes a wealthy theological and magisterial tradition about social economic and political issues. Starting with the Scriptures, it establishes itself in the Patristic and goes forward in the Middle Ages, continuing until present days. As part of these Teachings, and starting with Pope Leo XIII’s Rerum Novarum Encyclic, in 1891, a set of Pontifical Documents, produced by the subsequent Popes was created. This we call the Social Doctrine of the Church and in it we perceive a certain unity and coherence. At the same time, however, we find in the Social Doctrine of the Church some paradigmatic changes overtime that show a non-linear development of this Doctrine. In this article we seek to emphasize how Pope Francis, in his Pontificate, inaugurated a new paradigm in the Social Doctrine of the Church, linking the social political and economic issues to the environmental one and we attempt to analyze its meaning.